ANTOLOGI CERPEN INDONESIA-MALAYSIA SEBAGAI MATERI PEMBELAJARAN SASTRA DI SMA: KAJIAN SOSIOLOGI SASTRA DAN NILAI BUDI PEKERTI - Halimah Nur Rohmah; Ani Rakhmawati; Budhi Setiawan (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This research is descriptive qualitative research with approach of sociology of literature. Data collection techniques used in this study are document analysis techniques and interviews. Data validity uses data triangulation and source triangulation. Data analysis using interactive analysis method with the stages of data collection, data reduction, data presentation, and conclusion. The results of this study indicate that (1) the author's most dominant social setting influences the creation of literary works, namely the educational background and the profession of the author. (2) The description of the community reflected in the ACIM includes: stunting in life, issues of tolerance, doubts about defending the homeland, the dissolution of national language, cultural issues, and the phenomenon of early marriage. (3) the response of ACIM readers states that this anthology is interesting in terms of the language, theme and background of the formation of two state anthologies. (4) the values of character contained in ACIM include; religious, responsibility, hard work, respect, polite, ecological, nationalist, and action oriented. (5) ACIM can be used as a literary teaching material in high schools in accordance with the basic competencies (KD) of short stories, this anthology can also be used as literary learning material in terms of aspects of language, psychology, and cultural background.